1991
DOI: 10.1007/bf00046840
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion molecules of the immunoglobulin supergene family and their role in malignant transformation and progression to metastatic disease

Abstract: Cell adhesion molecules (CAMs) of the immunoglobulin supergene family may play important roles in tumorigenesis and the development of metastatic disease. In a variety of human malignancies, tumor progression has been observed to be associated with changes in CAM expression. An early event in colorectal tumorigenesis appears to be the down regulation of a normally expressed CAM, DCC. Over-expression of a second CAM, carcinoembryonic antigen, is associated with colorectal tumors which have a high risk for metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
6

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(60 citation statements)
references
References 44 publications
3
51
0
6
Order By: Relevance
“…Thus, our results suggest the possibility that CAM expression could be related to differences in spontaneous aggressiveness. These results are in agreement with various reports showing that high levels of CD54 were associated with aggressive tumours, such as high grade NHL, 31,37 progressive melanomas 38 and advanced stage transitional cell bladder cancer. 39 Strong expression of CD11a has been demonstrated in both highly aggressive and indolent tumours, such as active myeloma 40 and low grade NHL, 8,41 respectively.…”
Section: Figuresupporting
confidence: 93%
“…Thus, our results suggest the possibility that CAM expression could be related to differences in spontaneous aggressiveness. These results are in agreement with various reports showing that high levels of CD54 were associated with aggressive tumours, such as high grade NHL, 31,37 progressive melanomas 38 and advanced stage transitional cell bladder cancer. 39 Strong expression of CD11a has been demonstrated in both highly aggressive and indolent tumours, such as active myeloma 40 and low grade NHL, 8,41 respectively.…”
Section: Figuresupporting
confidence: 93%
“…It is postulated that ICAM-1 expression on tumour cells may mediate their attachment to activated leukocytes, promote the migration of individual cells away from the primary tumour and enhance endothelial binding, extravasation and invasion into surrounding tissues (Johnson, 1991). In contrast, other investigators have reported a negative correlation between ICAM-1 expression and tumour growth and metastasis in colorectal cancer and breast cancer and found that patients with ICAM-1-positive tumours had a better prognosis than those whose tumours did not (Shibata et al, 1996;Ogawa et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Tumour progression is associated with changes in the expression of cellular adhesion molecules which accompany the disaggregation of individual cells from the primary tumour and their penetration through the basement membrane, migration through the blood or lymph vessels, and attachment to a distant site (Johnson, 1991). Adhesion molecules are also required to provide 'co-stimulatory' antigenindependent interactions between leukocytes and target cells in the initiation of a cellular immune response against tumour cells (Springer, 1990).…”
mentioning
confidence: 99%
“…The metastatic cells have been characterized by extensive expression of matrix metalloproteinases (MMPs) [3], adhesion-related molecules [4] and activation of epithelial-to-mesenchymal transition (EMT) pathway [5] during malignant progression to increase tumor cell motility and invasiveness. To study the underlying mechanisms of the metastatic cells, in vitro models are preferred candidates when eliminating variables and decreasing intraexperimental variability.…”
Section: Introductionmentioning
confidence: 99%